PATHOPHYSIOLOGICAL ROLE OF ADIPONECTIN IN THE DEVELOPMENT OF OBESITY AND ASSOCIATED DISEASES - Kobylyak, N.M.; Savchenyuk, O.A.; Virchenko, O.; Falalyeyeva, T.M. (World of Medicine and Biology, 2013)
The analysis of scientific data on the mechanisms of action of adiponectin and its role in metabolism and in the pathogenesis of diseases was represented in this article. It was shown decrease in glucose, triglycerides, low-density lipoprotein level in blood under the influence of adiponectin. Reduced adiponectin concentration in blood was observed in obesity, insulin resistance, nonalcoholic steatohepatitis, atherosclerosis and endothelial dysfunction. Thus, given the range of adiponectin action, activation of intracellular cascades mediated by this hormone creates a field of investigation for search and implementation effective therapeutic agents for the treatment of the above diseases.